Aggregatibacter actinomycetemcomitans infection causes DNA double‐strand breaks in host cells. (14th February 2018) - Teshima, Rie; Hanada, Katsuhiro; Akada, Junko; Kawano, Kenji; Yamaoka, Yoshio
Abstract : Periodontal disease, an inflammatory disease, is caused by infection with periodontal pathogens. Long‐term periodontal disease increases the risk of oral carcinogenesis. Similar to other peptic cancers, oral carcinogenesis also requires multiple genome instabilities; however, the risk factors related to the accumulation of genome instabilities are poorly understood. Here, we suggested that specific periodontal pathogens may increase the risk of genome instability. Accordingly, we screened several periodontal pathogens based on the ability to induce DNA double‐strand breaks (DSBs) in host cells. We found that Aggregatibacter actinomycetemcomitans Y4 infection induced DSB formation in host cells. To assess whether DSB formation induced by infection with A. actinomycetemcomitans occurred through apoptotic chromosome fragmentation, cells were treated with a caspase inhibitor, Z‐VAD‐FMK. DSB accumulation induced by infection with A. actinomycetemcomitans was observed, even in the presence of Z‐VAD‐FMK, suggesting that this breakage occurred independently of apoptosis. These results suggested that some periodontal pathogens can increase the risk of genome instabilities in host cells and subsequently increase the risk of carcinogenesis. Abstract : DNA double‐strand breaks were accumulated in host cell after infection with A. actinomycetemcomitans Y4. The accumulation of DSBs following infection with A. actinomycetemcomitans was independent of apoptotic chromosomal fragmentation. A. actinomycetemcomitans infection induces inflammatory responses in host cells.